Synthesis of TiO2 Thin Film with Cobalt Doping Using Sol-Gel Spin-Coating Technique as a Solar Cell Material - Satipa, Denda Anung; Harpani, Baiq Fara Audy; Sani, Hadijah Mutiara; Wati, Eka Prasetia; Martiana, Rina; Doyan, Aris; Susilawati, Susilawati; Rizaldi, Dedi Riyan; Fatimah, Ziadatul (AMPLITUDO : Journal of Science and Technology Innovation, 2024)
Research has been done on thin films by mixing TiO2 with cobalt doping and adding HCI as a solar cell material. The aim of this research is to produce a thin layer that is good for use in solar cells. This research has several stages, namely: 1) weighing cobalt and titanium; 2) glass substrate preparation; 3) making a sol-gel solution; 4) thin layer deposition; and 5) heating the sample. From these several stages, the result was that a pure TiO2 solution without doping obtained a thick white solution, whereas the more doping used, the fainter the color of the solution obtained. The thin-layer synthesis process uses a spin-coating method assisted by a modified centrifuge to evenly distribute the sol-gel solution on the surface of the glass substrate